2018
DOI: 10.1111/jbg.12369
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for population structure in selective cow genotyping strategies

Abstract: The objective of the present study was to investigate the impact of considering population structure in cow genotyping strategies over the accuracy and bias of genomic predictions. A small dairy cattle population was simulated to address these objectives. Based on four main traditional designs (random, top‐yield, extreme‐yield and top‐accuracy cows), different numbers (1,000; 2,000 and 5,000) of cows were sampled and included in the reference population. Traditional designs were replicated considering or not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
7
0
2
Order By: Relevance
“…However, with the IBD‐GS approach, they suggested that with small inflation, bias would not be a problem in practice. Similarly, high bias of prediction of GEBV was also obtained for extreme phenotypic selective genotyping by Perez et al (). High bias of prediction in B25 and B50 was due to their minimal contribution to the subsequent generations.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, with the IBD‐GS approach, they suggested that with small inflation, bias would not be a problem in practice. Similarly, high bias of prediction of GEBV was also obtained for extreme phenotypic selective genotyping by Perez et al (). High bias of prediction in B25 and B50 was due to their minimal contribution to the subsequent generations.…”
Section: Discussionmentioning
confidence: 63%
“…Ødegård and Meuwissen () have studied the advantages of identity by descent genomic selection and found that inclusion of 5% most extreme sibs in the reference results in the extra genetic gain. Perez et al () studied the female selective genotyping strategy in GS. They reported that inclusion of extreme cow (pseudo) phenotypes in the reference is useful to accurately predict the most influential SNPs in genome‐wide association studies; however, the estimates of GEBVs were highly inflated in selection candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of females in the genotyped population was also found to be beneficial in species where the effect of female paths on genetic progress is strong, and the effect of genomic data on accuracy depends on the existing population structure (Lourenco et al, 2015). The effect of genotyped populations including female genomic information on genomic prediction accuracy has been thoroughly studied (Koivula et al, 2016;Uemoto et al, 2017;Perez et al, 2019), and also as a strategy to increase the genotyped population size into small populations (Jiménez-Montero et al, 2012;Lund et al, 2016;Jenko et al, 2017). Different strategies have been proposed to assess an optimal selection of individ-uals to be genotyped.…”
Section: Maximum Genotypingmentioning
confidence: 99%
“…Different strategies have been proposed to assess an optimal selection of individ-uals to be genotyped. Including genomic information of females selected based on a divergent strategy seems to be better than a random or directional approach (Jenko et al, 2017;Perez et al, 2019), and avoiding the inclusion of only selected individuals would reduce prediction bias (Vitezica et al, 2011;Koivula et al, 2016). In practical terms not all the strategies are feasible for animal breeding programs and even less for small populations.…”
Section: Maximum Genotypingmentioning
confidence: 99%
“…Newborn bull-calves aged 8, 12, and 15 months were by the conventional method examined on the main measurements on the basis of which body-build indices were calculated [7].…”
Section: Methodsmentioning
confidence: 99%